STRATEGI PEMANFAATAN INFORMASI IKLIM UNTUK KETAHANAN PANGAN BERKELANJUTAN DI KECAMATAN SUNGAI BATANG - Burhanudin Burhanudin; Mubarak Mubarak; Imam Suprayogi (Jurnal Zona, 2023)
Riau Province is known to have agricultural resources that have the potential to become a national food barn. The Riau region which has great potential is the Indragiri Hilir Region. However, in recent years, rice production from the region has decreased. This is caused by various factors, one of which is the lack of understanding of farmers about climate information so that they cannot carry out mitigation and adaptation. For this reason, this study aims to determine the strategy for utilizing climate information so that food availability in Sungai Batang Regency is guaranteed to be sustainable. This research was conducted in March - May 2023 in Sungai Batang District, Indragiri Hilir Regency. The data used in this research comes from primary and secondary data. Analysis of the data used in the form of descriptive analysis and SWOT analysis. The results of this study indicate that the strategy used in this study is the S-T (Strength – Threat) strategy. This strategy is a combination of internal factors, namely strength factors and external factors, namely threat factors. From this strategy, the authors can recommend several programs that can be used to maintain food security in Sungai Batang District.